Factors associated with the blood lipid profile of patients in the Montes de Oca health service area in Costa Rica - Gutiérrez Peña, Erick G.; Romero Zúñiga, Juan José (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2011)
This study is aimed at analyzing the association between alterations in the blood lipid profile (dyslipidemia) and the exposure to socioeconomic, biotype and pathological conditions in patients in the Montes de Oca Health Service Area. A case-control study was conducted with a total of 135 cases and 135 controls that were between 20 and 65 years of age and were tested in 2006 for a blood lipid profile. Variables analyzed were: age, sex, body mass index, insurance type and presence of arterial hypertension, diabetes mellitus or both chronic pathologies simultaneously. A univariate analysis was followed by a multivariate analysis using a multiple logistic model. The only variable associated with dyslipidemia was body mass index in both the univariate and multivariate analyses. The rest of the variables showed no statistical association. Patients with higher body mass index exhibit a higher risk of an altered blood lipid profile.